(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Marianna A. Gulyaeva (Volgograd State Social-Pedagogical University, Volgograd, Russian Federation) The article investigates the phenomenon of refusal from communication in terms of its positive and negative impact, both on the communicative process, and interpersonal relationships in general. It has been analyzed several aspects of the failure to communicate with positive communication position. The identification of constructive or destructive potential was carried out on the basis of three parameters such as productivity/ unproductive conflict resolution with the help of avoiding communication, the choice of an optimum way of non-communication and its role in the communication process on the basis of the functions performed by them. Failure to communicate is often perceived negatively and is considered an inefficient form of communication, so it does not allow to solve interpersonal conflicts. This article discusses the circumstances where refusal from communication advocates an effective way to avoid conflict. In situations where the termination of communication is inevitable, a fundamental factor for the positive, harmonious form of communication acts interrupting the communication process. Functioning in the communicative space, failure to communicate can either destroy an interaction and relationship between the partners, and regulate the communication process by guiding in the right direction, coordinating the behavior of communication. Key words: refusal from communication, communication termination, positive communication, interpersonal communication, polite refusal, impolite refusal. DOI: 10.18522/1995-0640-2016-4-59-68